Pengaruh kinerja pegawai terhadap kepuasan warga binaan pemasyarakatan di Lembaga Pemasyarakatan Kelas IIA Tanjung Pinang: The effect of employee performance on the satisfaction of correctional asssisted citizens in Tanjung Pinang Class IIA Correctional Institution - Redho Karunia As'at; Nazaki; Ryan Anggria Pratama (JOURNAL OF GOVERNMENT SCIENCE, 2023)
Penitentiary is a public institution that plays an important role in carrying out state duties in terms of correctional and inmate development. However, in its implementation, the government apparatus, especially within the Penitentiary, is still ineffective and efficient, and there are still many problems that have not been resolved, such as the results of Hamzah's interview with former prisoners in Tanjungpinang Class IIA Prison. The purpose of the study was to determine whether there is an influence between employee performance and the satisfaction of correctional assisted citizens. The approach used in this study is a Quantitative approach, using Kumorotomo's theory, namely: efficiency, effectiveness, fairness, and responsiveness, and indicators from PERMENPAN No. 14 of 2017. The study population was correctional assisted citizens who received services at the Tanjungpinang Class IIA Correctional Office with a total of 520 people. The number of samples taken was 81 people, based on the calculation of the slovin formula with a tolerable margin of error of 10%. The results showed that none of the services had any influence on the independent variable and the dependent variable, with the value of F calculated = 0.213 with a significance level of 0.645 > 0.05 so that Ho was acceptable and H1 was rejected